Phylogeography of a Widely Distributed Atlantic Species: The Case of the Ghost Crab Ocypode quadrata (Fabricius, 1787) (Decapoda: Brachyura: Ocypodidae) - Tamburus, Ana Francisca [UNESP]; Miranda, Ivana [UNESP]; Naves, Bárbara Benati; Mantelatto, Fernando Luis (MDPI, 2024)
Ocypode Weber, 1795 (Brachyura: Ocypodidae) is popularly known as ghost crab, and encompasses 21 valid species, including Ocypode quadrata (Fabricius, 1787). This species has wide distribution along the Atlantic coast of America, from the USA (Massachusetts) to Brazil (Rio Grande do Sul), Central America, and Antilles. Such distribution, along with some biological characteristics of its life cycle and the presence of geographic barriers, could lead to genetic structuring. Herein, we evaluate the hypothesis of the presence of geographic barriers using COI and 16S partial gene fragments. The Maximum Likelihood tree suggests the monophyly of O. quadrata, while the values of intraspecific genetic distance along with the star-shaped haplotype network suggested a lack of genetic structure in Brazilian, Panama, and French Guiana populations, probably caused by larval dispersion. USA and Mexico populations may be a new lineage, but we cannot say it with few sequences and with no morphological characters.